Crimes of dissent : civil disobedience, criminal justice, and the politics of conscience - Lovell, Jarret S. (Alternative criminology series., 2009)
From animal rights to anti-abortion, from tax resistance to anti-poverty, activists from across the political spectrum often deliberately break the law to further their causes. While not behaviors common to hardened or self-seeking criminals, the staging of civil disobedience, non-violent resistance, and direct action can nevertheless trigger a harsh response from law enforcement, with those arrested risking jail time and criminal records. Crimes of Dissent features the voices of these activists, presenting a fascinating insider?s look at the motivations, costs and consequences of deliberately.